Linking Ecology to Genetics to Better Understand Adaptation and Evolution: A Review in Marine Macrophytes - Hu, Zi-Min; Zhong, Kai-Le; Weinberger, Florian; Duan, De-Lin; Draisma, Stefano G. A.; Serrão, Ester A. (Frontiers in Marine Science, 2020)
Ecological processes and intra-specific genetic diversity reciprocally affect each other. While the importance of uniting ecological variables and genetic variation to understand species’ plasticity, adaptation, and evolution, is increasingly recognized, only few studies have attempted to address the intersection of population ecology and genetics using marine macrophyte as models. Representative empirical case studies on genetic diversity are reviewed that explore ecological and evolutionary processes in marine macrophytes. These include studies on environment-induced phenotypic plasticity and associated ecological adaptation; population genetic variation and structuring driven by ecological variation; and ecological consequences mediated by intraspecific and interspecific diversity. Knowledge gaps are also discussed that impede the connection of ecology and genetics in macrophytes and possible approaches to address these issues. Finally, an eco-evolutionary perspective is advocated, by incorporating structural-to-functional genomics and life cycle complexity, to increase the understanding of the adaptation and evolution of macrophytes in response to environmental heterogeneity.